Kontribusi Pendapatan Perempuan Pedagang Sayuran Dalam Keluarga Di Pasar Tompaso Baru Kabupaten Minahasa Selatan - Eunike Felmi Iren Pesik; Benu Olfie Liesje Suzana; Jenny Baroleh (AGRI-SOSIOEKONOMI, 2022)
The research aims to determine and analyse the income contribution of women vegetable sellers to families at Tompasobaru Market, South Minahasa Regency. The research was carried out for 2 months, from January to February 2022. The data collected in this study is primary data obtained from direct interviews with women who sell vegetables using a questionnaire. Secondary data was obtained from the village office and market office, as well as research-related data taken from the internet. In this study the number of respondents was 9 female vegetable sellers who met the requirements who were randomly selected purposive sampling. The results showed that the income contribution of women vegetable sellers at Tompasobaru market to family income was 43.28% with at average income of Rp 2.667.778/month. The income of women vegetable sellers can generate additional/main income in the family in their role in public spaces (outside the come).